Efficiency Assessment of Slovakian Universities - Grausová, Mária; Hužvár, Miroslav; Rigová, Zuzanna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper studies the performance of public higher education institutions in Slovakia. Data envelopment analysis is applied to assess the efficiency of selected universities in their two core mission areas: providing education and doing research and development. We focus on how the size and the structure of the academic staff and the capital resources influence the educational and research outputs. Data from public sources for years 2014 – 2015 is used in the analysis. Efficiency scores and projections calculated by designed DEA models serve to benchmark assessed universities and provide recommendations for improvement of their performance
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 195-206
Keywords: data envelopment analysis; efficiency; public higher education institutions